2006
DOI: 10.3139/146.101381
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tension–compression loading history on plastic deformation of Mg wrought alloy AZ31

Abstract: The plastic deformation behavior of the Mg wrought alloy AZ31 is investigated in tension–compression tests at room temperature. It strongly depends on the loading direction and is characterized by dislocation slip as well as by the formation of deformation twins. The latter is reversible in the case of a change of the deformation direction. Because of the pronounced crystallographic texture of the material investigated, a macroscopic deformation anisotropy exists with lower flow stresses in compression than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Scholtes [38] who considered the impediment of the formation of twins and detwining processes with increasing cycles. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholtes [38] who considered the impediment of the formation of twins and detwining processes with increasing cycles. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, an asymmetric sigmoidal-shaped loop appeared. The major deformation characteristics associated with the twinning-detwinning mechanism in magnesium alloys have been reported in [37][38][39][40] as well. It was also reported that more twinning occurred as the cycle increased but will halt at a certain number of cycles [15], hence the compressive load decreased with increasing twins while the tensile load increased with the greater detwinning process as seen from Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Recently, a number of studies have been performed to understand the low-cycle fatigue performance of wrought magnesium alloys [5][6][7][8][9][10][11][12][13][14][15] and their associated cyclic plastic deformation [3,[16][17][18][19][20][21], including details characteristic of twinning and detwinning behavior [22][23][24][25][26][27]. These reports document the fact that low-cycle fatigue resistance and the cyclic response including cyclic stress evolution and cyclic stress-strain behavior are affected by various microstructure parameters.…”
Section: Introductionmentioning
confidence: 97%
“…The larger the compressive predeformation and thus, the amount of twins, the larger is the deviation from linearity at the beginning of a reversal. It can be seen in both studies [34,35] that the shapes of reversals at variable amplitude loading depend on several parameters such as mean strain, predeformation and strain amplitude. Nevertheless, experimentally determined hysteresis loops were evaluated without consideration of an adequate stress-strain model in [34,35].…”
Section: Introductionmentioning
confidence: 97%
“…http Zenner and Renner [34] analyzed the shape of hysteresis loops at variable amplitude loading and showed that different magnesium alloys exhibit material memory. Götting and Scholtes [35] investigated the influence of strain-controlled loading history on the stress-strain behavior of AZ31 wrought magnesium alloy and found the shape of the reversals to be strongly influenced by predeformation. The larger the compressive predeformation and thus, the amount of twins, the larger is the deviation from linearity at the beginning of a reversal.…”
Section: Introductionmentioning
confidence: 99%